AMELIORATIVE EFFECTS OF HYDROALCOHOLIC OCIMUM BASILICUM LEAF EXTRACT ON BIOCHEMICAL AND HISTOLOGICAL ALTERATIONS IN CISPLATIN-INDUCED CARDIOTOXICITY IN MALE WISTAR RATS - Tarigan, Novitasari; Dianda, Feby; Lister, I. Nyoman Ehrich; Fachrial, Edy (International Archives of Medical Sciences and Public Health, 2025)
Cardiotoxicity is a common side effect of cisplatin (CIS) chemotherapy, often accompanied by gastrointestinal, renal, and hematological toxicities. This study investigated cardioprotective potential of hydroalcoholic basil leaf extract against CIS-induced toxicity in rats, evaluated through Troponin-T, high-sensitivity C-reactive protein (Hs-CRP), superoxide dismutase (SOD), malondialdehyde (MDA) levels, and cardiac histopathology. A quasi-experimental design was employed with eight groups of rats (n = 6 per group): normal, negative control, positive control (vitamin C), and treatment groups receiving basil extract (400 and 800 mg/kg body weight). CIS administration significantly elevated Troponin-T, Hs-CRP, and MDA levels while reducing SOD activity. Treatment with basil extract, particularly at 800 mg/kg, markedly attenuated these changes, restoring biochemical markers toward normal values. Histopathological analysis further confirmed the cardioprotective effect. In conclusion, basil leaf extract demonstrates promising potential as a cardioprotective agent against CIS-induced cardiotoxicity.